2002
DOI: 10.1596/1813-9450-2850
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Commercial Bank Performance in Transition: An Application of Data Envelopment Analysis

Abstract: Banking sectors in transition economies have variables. In addition to stressing the importance of some experienced major transformations throughout the bank-specific variables, the censored Tobit analysis 1990s. While some countries have been successful in suggests that: eliminating underlying distortions and restructuring their * Foreign ownership with controlling power and financial sectors, in some cases financial sectors remain enterprise restructuring enhance commercial bank underdeveloped and the rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
56
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(72 citation statements)
references
References 40 publications
14
56
1
1
Order By: Relevance
“…The authors investigated the bank performance in the period of 1988 to 1995 in 80 countries and the result indicated differences in bank characteristics and macroeconomic variables as the determinants of net interest margin and bank profitability. In another panel country study, Grigorian and Manole (2002) investigated efficiency in commercial bank operations in transition countries in the period of 1995 to 1998. The study reported that foreign ownership and consolidation of banks enhanced commercial bank efficiency in transition countries.…”
Section: Determinants Of Bank Performancementioning
confidence: 99%
“…The authors investigated the bank performance in the period of 1988 to 1995 in 80 countries and the result indicated differences in bank characteristics and macroeconomic variables as the determinants of net interest margin and bank profitability. In another panel country study, Grigorian and Manole (2002) investigated efficiency in commercial bank operations in transition countries in the period of 1995 to 1998. The study reported that foreign ownership and consolidation of banks enhanced commercial bank efficiency in transition countries.…”
Section: Determinants Of Bank Performancementioning
confidence: 99%
“…It is found that majority foreign-owned banks (defined as those banks in which foreigners held more than 50 percent of equity) were more efficient than majority domestic privatelyowned banks, which in turn were more efficient than majority domestic government-owned banks. Grigorian and Manole (2006) consider the determinants of bank performance in 17 eastern and central European economies over the period 1995-1998. They also first compute efficiency scores, except using data envelopment analysis (DEA) rather than SFA, before performing a second stage regression.…”
Section: Literature Review: Foreign Ownership and Bank Performancementioning
confidence: 99%
“…Foreign ownership was again found to be positively related to bank efficiency. Findings of the likes of Bonin et al (2005) and Grigorian and Manole (2006) serve to provide optimism regarding the impact that foreign investment might have had in the Chinese context. They do not, however, allow strong a priori expectations to be formed given that no Chinese bank has sold more than 30 percent of its equity to foreign investors.…”
Section: Literature Review: Foreign Ownership and Bank Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The growth rate of economic development may positively influence the quality and the skill levels of banks (Claessens et al, 2001). INFL is included to capture potential inefficiencies due to price (high interest margin) and nonprice (excessive branches) behaviour of banks (Grigorian and Manole, 2002). INTR is used as a control variable in the cost function since interest costs are an important part of total banking costs (Fries and Taci, 2005).…”
mentioning
confidence: 99%